Unconventional Secretion of Plant Extracellular Vesicles and Their Benefits to Human Health: A Mini Review - Farley, Joshua T.; Eldahshoury, Mahmoud K.; de Marcos Lousa, Carine (Frontiers in Cell and Developmental Biology, 2022)
Mechanisms devoted to the secretion of proteins via extracellular vesicles (EVs) have been found in mammals, yeasts, and plants. Since they transport a number of leader-less proteins to the plasma membrane or the extracellular space, EVs are considered part of Unconventional protein secretion (UPS) routes. UPS involving EVs are a relatively new field in plants. Aside from their role in plant physiology and immunity, plant extracts containing EVs have also been shown to be beneficial for human health. Therefore, exploring the use of plant EVs in biomedicine and their potential as drug delivery tools is an exciting avenue. Here we give a summary of the state of knowledge on plant EVs, their crosstalk with mammalian systems and potential research routes that could lead to practical applications in therapeutic drug delivery. Abbreviations: EVs: extracellular vesicles; ER, endoplasmic reticulum; PM, plasma membrane; MVB: multivesicular body; TGN, trans-Golgi network; EE, Early endosome; ILVs, Intraluminal vesicles.